The Effect of Occasional Alcohol Drinking on Semen Quality and Sperm Morphology among Young and Healthy Polish Men - Felicja Lwow; Marek Medraś; Małgorzata Słowińska-Lisowska; Paweł Jóźków; Leszek Szmigiero (Journal of Men's Health, 2017)
ABSTRACT